Pd(II)-mediated triad multilayers with zinc tetrapyridylporphyrin and pyridine-functionalized nano-TiO2 as linkers assembly, characterization, and photocatalytic properties - Ren, Xue-Bing (Langmuir : the ACS journal of surfaces and colloids, 2012)
Triad hybrid multilayers containing the light sensitizers of zinc tetrapyridylporphyrin (ZnTPyP) and pyridine-functionalized TiO(2) (TiO(2)-Py) nanoparticles were constructed on substrate surfaces with the use of Pd(II) ions as the connectors using the layer-by-layer (LBL) method. The assembly process was monitored using ultraviolet-visible (UV-vis) absorption and X-ray photoelectron spectra as well as scanning electron microscopy and atomic force microscopy. The content of the pyridine substituents in the TiO(2)-Py nanocomposites was about 2% (w/w). The Soret absorption band of ZnTPyP was 24 nm red-shifted in the hybrid multilayers due to a strong intermolecular electronic coupling interaction among porphyrin macrocycles or porphyrin macrocycle/TiO(2)-Py nanoparticles. The average surface density of each ZnTPyP layer was about 1.4 × 10(-10) mol/cm(2). Aggregation of the small TiO(2)-Py nanoparticles to larger domains with sizes up to hundreds of nanometers occurred in the hybrid multilayers; however, such an aggregation behavior was weaker than that in the solutions. The quartz substrate modified with the as-prepared Pd/ZnTPyP/Pd/TiO(2)-Py triad hybrid multilayers was used as a heterogeneous photocatalyst for the degradation of methyl orange (MO) under irradiation (λ > 420 nm) at room temperature with a catalytic efficiency of about 1.3 × 10(-3) MO/ZnTPyP·s. Without the use of the filter, the catalytic efficiency increased because both ZnTPyP and TiO(2)-Py nanocomposites acted as the light sensitizers. It is suggested that the present heterogeneous catalyst has the advantages of facile separation, high stability, structural controllability on the molecular and nanoscale level, and good recyclability